Pengaruh Variasi Sampah Plastik Jenis High Density Polyethylene (HDPE), Low Density Polythylene (LDPE), dan Polypropylene (PP) Terhadap Volume Minyak Hasil Pirolisis - Minduro, Manshuriin; Suarnadwipa, I Nengah; Astawa, Ketut (Teknik Desain Mekanika; Vol 13 No 3 (2024): Juli 2024 : Teknik Desain Mekanika, 2024)
Abstractt Plastic waste is one of the biggest sources of environmental pollution problems. Plastic is a category of inorganic waste that can have positive or even negative impacts on the lives of living creatures if it is not used and handled in the right way. As a result of this, efforts are needed to overcome the threat of plastic waste using the 3R (Reduce, Reuse, Recycle) method. In this research, one of the applications of reuse is using the pyrolysis method, namely processing plastic waste into alternative fuel that can be reused. This pyrolysis research was carried out using 3 types of plastic waste, namely, High Density Polyethylene (HDPE), Low Density Polythylene (LDPE), and shredded Polypropylene (PP). This test uses a mass of 1 kg of plastic waste for each type of plastic waste and uses a reactor temperature of 400?. This research focuses on the influence of variations in each plastic waste on the performance of the pyrolysis system. The results obtained from the pyrolysis test are The volume of oil produced from the three types of plastic waste is HDPE 400 mL, LDPE 449 mL, and PP 921. Keywords: Pyrolysis, variations in plastic waste HDPE, LDPE, dan PP, oil volume